Empirical analysis of big data analytics adoption in Malaysian SMEs: a TOE model approach - Muhamad Ibrahim, Najhan; Bashir, Salman (IEEE, 2026)
This research investigates the adoption of Big Data Analytics (BDA) within Small and Medium-sized Enterprises (SMEs) in Malaysia, leveraging the Technology-OrganizationEnvironment (TOE) model as a conceptual framework. A comprehensive review of global TOE factors SMEs face sets the stage for understanding the context of BDA adoption. The study employs a structured questionnaire survey, gathering responses from 155 SMES personnel to assess diverse TOE factors and the impact of BDA adoption. The findings reveal a positive correlation between BDA adoption and its Relative Advantages: cost reduction, improved work processes, elevated customer service, and enhanced work quality. Significant influencers in the adaptation of BDA within SMEs include Compatibility and Complexity. Organizational factors, such as preparedness and top-level management support, emerge as critical variables shaping BDA adoption. Furthermore, environmental factors, particularly competitive pressure, outweigh governmental regulation as a driver for BDA adoption among SMEs in Malaysia. Employing SPSS software and one-sample t-test analysis, the study establishes statistical significance for each identified TOE factor, providing robust evidence of their impact in the Malaysian SMES context. This research contributes empirical insights into the nuanced dynamics of BDA adoption, offering valuable guidance for policymakers, practitioners, and researchers navigating the evolving landscape of digital transformation within SMEs.